Space, Place, Haven: Levinas’s Phenomenology of Home - Saldukaitytė, Jolanta (Problemos, 2020)
By distinguishing between space and place, the article situates and analyses the meaning of the closest place – home – in the philosophy of Emmanuel Levinas. The effort to encounter transcendence, to escape, to leave, to not be attached a particular place, and not to be driven by a nostalgia to return, is dominant in Levinas’s philosophy. This article shows that dwelling in a place, as settling in a home, also has a positive meaning for Levinas. This positive meaning comes, however, not from an ontological but from an ethical relationship with a place. The home is shown as chosen place, warm and human, as opposed to a given or natural place. On the one hand, the home is a necessary condition for security, but also the very condition of interiority and activity, of having the place in the world in contrast to thrownness. On the other hand, it is not a place where I is embodied and rooted in like a vegetable, but a place where I welcome the other.